Spontaneous Colo-Umbilical Fistula Complicating Diverticulitis of the Sigmoid Colon. (6th June 2013) - Bolanaki, Helen; Kouklakis, Georgios; Courcoutsakis, Nikos; Oikonomou, Panagoula; Karayiannakis, Anastasios J.
Abstract : Colocutaneous fistula caused by diverticulitis is relatively uncommon with colo-umbilical fistulas being even rarer. We herein report a rare case of a spontaneous colo-umbilical fistula due to diverticulitis of the sigmoid colon. The fistula developed from a diverticulum of the sigmoid colon that discharged through the umbilicus after two episodes of acute diverticulitis. The condition was successfully treated by resectional surgery.